2006
DOI: 10.1111/j.1742-4658.2006.05558.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytochelatin–cadmium–sulfide high‐molecular‐mass complexes of Euglena gracilis

Abstract: High‐molecular‐mass PC complexes (PC‐HMWCs) constituted by phytochelatins (PCs), cadmium and sulfide are synthesized by several organisms after exposure to cadmium. In this study, PC‐HMWCs were isolated from photoheterotrophic Euglena gracilis and purified to homogeneity, resulting in compounds of molecular mass 50–380 kDa depending on the CdCl2 and sulfate concentrations in the culture medium. In contrast with plants and some yeasts, PC‐HMWCs from E. gracilis mainly comprise (57–75%) monothiol molecules (Cys,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 34 publications
(71 reference statements)
2
16
0
Order By: Relevance
“…It is an Mg-ATP-dependent glutathione S-conjugate transporter responsible for vacuolar sequestration of GSH-metal complexes, that transport bis (glutathionato) cadmium (Cd-GS 2 ) into vacuoles [19,111], as well as As-GS 3 [112] and Hg-GS 2 [113]. Recently, Mendoza-Cozatl et al [114] showed the presence of PC-HMW complexes in chloroplasts of Euglena gracilis, suggesting role of chloroplast in Cd resistance mechanism in organisms lacking a plant-like vacuole (Fig. 6).…”
Section: Vacuolar Sequestration Of Pc-metal Complexes and Role Of Sulmentioning
confidence: 98%
“…It is an Mg-ATP-dependent glutathione S-conjugate transporter responsible for vacuolar sequestration of GSH-metal complexes, that transport bis (glutathionato) cadmium (Cd-GS 2 ) into vacuoles [19,111], as well as As-GS 3 [112] and Hg-GS 2 [113]. Recently, Mendoza-Cozatl et al [114] showed the presence of PC-HMW complexes in chloroplasts of Euglena gracilis, suggesting role of chloroplast in Cd resistance mechanism in organisms lacking a plant-like vacuole (Fig. 6).…”
Section: Vacuolar Sequestration Of Pc-metal Complexes and Role Of Sulmentioning
confidence: 98%
“…Keimowitz et al (2007), showed that this phenomenon could be utilized at landfill and other sites where As mobilization is a problem. While some eukaryotic microbes like Candida glabrata metabolizes extracellular sulfate to sulfide (Thomas and SurdinKerjan, 1997), that acts as an electron donor for As(V) reduction (Rochette et al, 2000), other yeast like Schizosaccharomyces pombe (Dameron and Winge, 1990) and C. glabrata (Krumov et al, 2007) incorporates sulfide to form a more stable, high molecular weight PC-metal-sulfide complex in the vacuole (Kneer and Zenk, 1997;Mendoza-Cozatl et al, 2006). Some microbes (e.g.…”
Section: Immobilization and Bioaccumulation/biosequestrationmentioning
confidence: 98%
“…It is known that sulfide present in soil decreases the toxicity of As by creating metal precipitates. Some eukaryotes also have taken this strategy by incorporating sulfide and forming a high molecular weight PC-metal-sulfide precipitation in the vacuole (Mendoza-Cozatl et al, 2006). However in the bacterial kingdom hydrogen sulfide production is only restricted to anaerobic sulfatereducing bacteria that produce H 2 S only under strict anaerobic condition.…”
Section: Transgenic Plantsmentioning
confidence: 99%
“…Non-essential heavy metals (e.g., lead, cadmium and mercury) and excessive essential heavy metals (e.g., zinc and copper) can have many deleterious eff ects on plants, such as chlorosis, necrosis, accelerated aging, and changes in ionome and hormonal status (Lequeux et al, 2010;Pandey and Singh, 2012). To detoxify non-essential or excessive essential heavy metals, high-affi nity substances with abundant thiol groups, such as phytochelatins (PCs), can be used to chelate, sequestrate and compartmentalize heavy metals (Mendoza-Cózatl et al, 2006).…”
Section: Introductionmentioning
confidence: 99%